School education and citizenship in rural Andean Peru: the communicative role of spatial organization - Grim-Feinberg, Kate (2012)
This article, based on fieldwork conducted in a primary school in Lucanas Province (Ayacucho, Peru), highlights the communicative role of children´s spatial organization in school line-ups. I suggest that school line-ups may be particularly emphasized in agricultural communities that have historically been left out of the national imaginary. The straight lines may be oriented toward forming children into citizen-subjects who are orderly, oriented toward progress, and united with an imagined national community. Furthermore, the spectacle form of school line-ups creates a connection between the norms of citizenship taught in school and the multiple spectacles in which children participate in communal agricultural life. These preliminary results draw attention to the importance of considering spatial organization both in and outside of school as a significant element in citizenship education and a key topic for reflection in the promotion of inclusive citizenship.